2006
DOI: 10.1177/0734016806287945
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Maltreatment Recurrence and Child Welfare Services on Dimensions of Delinquency

Abstract: The study examines the relationship between maltreatment recurrence and various dimensions of delinquency among a cohort of at-risk youths. The results indicate that maltreatment recurrence is a significant predictor of the initiation, continuation, and severity of delinquency. The relationship continues to exist in the presence of other delinquency risk factors. Within the maltreatment subgroup, a curvilinear pattern is observed. This pattern suggests that child welfare placement services reduce the effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(51 citation statements)
references
References 48 publications
5
45
1
Order By: Relevance
“…This seems counter-intuitive. Any link between maltreatment and delinquency is, however, complicated (Smith and Thornberry, 1995;Lemmon, 2006). Most previ ous literature does not measure number of maltreatment types, just whether maltreatment occurred and, sometimes, which type (Smith and Thornberry, 1995;Maxfield and Widom, 1996;Lemmon, 1999;Wiebush et al, 2000;Mersky and Reynolds, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This seems counter-intuitive. Any link between maltreatment and delinquency is, however, complicated (Smith and Thornberry, 1995;Lemmon, 2006). Most previ ous literature does not measure number of maltreatment types, just whether maltreatment occurred and, sometimes, which type (Smith and Thornberry, 1995;Maxfield and Widom, 1996;Lemmon, 1999;Wiebush et al, 2000;Mersky and Reynolds, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors in these circumstances tend to be cumulative and to have interactive effects, making delinquency prediction challenging for practitioners (Lemmon, 2006;Ford et al, 2007). A history of maltreatment has been shown to be signifi cant even in the presence of these other risk factors (Smith and Thornberry, 1995;Maxfield and Widom, 1996;Lemmon, 1999;Wiebush et al, 2000), although most studies have documented a general link, and studies investigating an asso ciation between types of maltreatment individually (physical abuse, sexual abuse and neglect) and delinquency have been limited (Currie and Tekin, 2006;Mersky and Reynolds, 2007).…”
Section: Maltreatment To Delinquency Linkmentioning
confidence: 99%
“…A number of studies have shown that the experience of family violence is common among youth who are chronic or persistent offenders (Arnull et al, 2005;Lemmon, 2006;MacRae, Bertrand, Paetsch, & Hornick, 2008). Recent literature from Australia (Stewart, Livingston, & Dennison, 2008) reveals that youth who experience maltreatment during adolescence are more likely to reoffend than those who experience maltreatment prior to adolescence.…”
Section: Family Factorsmentioning
confidence: 99%
“…Several studies have supported the link between increased risk of aggression and juvenile delinquency in victims of abuse and neglect (e.g., Hawkins et al, 1998;Lemmon, 2006;Mersky & Reynolds, 2007; Stouthamer- Loeber, Wei et al, 2002). For example, Lemmon (2006) found that maltreatment recurrence was a significant factor in explaining initiation, continuation, and severity of delinquency, even when statistically controlling for other factors such as social class, geographic location, and race. However, others have deemed the relationship between child maltreatment and delinquent behavior more complex.…”
Section: Child Maltreatment and Dependencymentioning
confidence: 99%